How Authoritative Parenting Shapes Religious Values in Early Childhood: Insights from PAUD Citra Harapan - Barokfi Mumtaz; Darmu'in Darmu'in; Agus Sutiyono (Jurnal Obsesi : Jurnal Pendidikan Anak Usia Dini, 2024)
This study examines the impact of authoritative parenting on children's religious attitudes. A qualitative phenomenological approach was used to collect data through observations and interviews with two families whose children were attending PAUD Citra Harapan in Semarang Regency. The credibility of the data was ensured through source and method triangulation. The analysis involved collecting, presenting, reducing, and concluding the phenomena experienced by the research subjects. The findings indicate that authoritative parenting is characterized by emotional support, warmth, and active parental involvement; religious values are taught through prayer, role modelling, and balanced discipline; and children raised with this parenting style demonstrate character traits such as empathy and responsibility. This study confirms the importance of authoritative parenting in fostering solid religious attitudes and social responsibility in children.